2015
DOI: 10.1002/2014jd021985
|View full text |Cite
|
Sign up to set email alerts
|

Global atmospheric sulfur budget under volcanically quiescent conditions: Aerosol‐chemistry‐climate model predictions and validation

Abstract: The global atmospheric sulfur budget and its emission dependence have been investigated using the coupled aerosol-chemistry-climate model SOCOL-AER. The aerosol module comprises gaseous and aqueous sulfur chemistry and comprehensive microphysics. The particle distribution is resolved by 40 size bins spanning radii from 0.39 nm to 3.2 μm, including size-dependent particle composition. Aerosol radiative properties required by the climate model are calculated online from the aerosol module. The model successfully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
203
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(214 citation statements)
references
References 101 publications
(171 reference statements)
10
203
1
Order By: Relevance
“…Previous studies suggested that OCS is a dominant contributor to the stratospheric aerosol layer during volcanically quiescent periods [Crutzen, 1976;Pitari et al, 2002]. This finding is corroborated by a recent model-based study that indicates that although 90% of the OCS transported into the stratosphere returns unprocessed to the troposphere, the remaining OCS contributes~56% to the stratospheric aerosol burden [Sheng et al, 2015]. There has been some debate, however, on the magnitude of the OCS flux to the stratosphere and on the relative contribution of OCS to the stratospheric aerosol loading [Brühl et al, 2012;Chin and Davis, 1995;Myhre et al, 2004].…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Previous studies suggested that OCS is a dominant contributor to the stratospheric aerosol layer during volcanically quiescent periods [Crutzen, 1976;Pitari et al, 2002]. This finding is corroborated by a recent model-based study that indicates that although 90% of the OCS transported into the stratosphere returns unprocessed to the troposphere, the remaining OCS contributes~56% to the stratospheric aerosol burden [Sheng et al, 2015]. There has been some debate, however, on the magnitude of the OCS flux to the stratosphere and on the relative contribution of OCS to the stratospheric aerosol loading [Brühl et al, 2012;Chin and Davis, 1995;Myhre et al, 2004].…”
Section: Introductionsupporting
confidence: 59%
“…A dominant indirect source results from CS 2 emissions from the rayon industry [Campbell et al, 2015]. With a tropospheric lifetime of~2-7 years [Blake et al, 2004], OCS is sufficiently long-lived in the troposphere that it is transported into the stratosphere where it is photooxidized to form sulfate particles [Sheng et al, 2015]. Previous studies suggested that OCS is a dominant contributor to the stratospheric aerosol layer during volcanically quiescent periods [Crutzen, 1976;Pitari et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…However, their analysis of the temporal trend of stratospheric OCS between 1978 and 2005 did not suggest that an increase in background levels of sulfate aerosol could arise from an increased OCS source (Coffey and Hannigan, 2010). Sheng et al (2015) have modelled the global atmospheric sulfur budget under volcanically quiescent conditions, including stratospheric processes and suggest that 30-40 Gg S a -1 in net is transferred across the tropopause, which is in line with the estimate of 35…”
Section: Accepted Manuscriptmentioning
confidence: 72%
“…Net fluxes to the stratosphere have been estimated in the range of 34-66 Gg S a -1 with a global stratospheric lifetime of 64 ± 21 a (Barkley et al, 2008;Sheng et al, 2015). Coffey and Hannigan (2010) examined conflicting claims about increases in the sulfate loading of the stratosphere from increasing OCS.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The total net sulphur mass flux from the troposphere into the stratosphere is estimated to be about 181 Gg S/yr 286 based on simulations by Sheng et al (2015a) using the SOCOL-AER model, 1.5 times larger than reported in 287 ASAP2006 (KTH2016). This estimate, however, could be highly dependent on the specific characteristics of the 288…”
Section: Motivation 285mentioning
confidence: 87%